2011
DOI: 10.1128/jvi.05039-11
|View full text |Cite
|
Sign up to set email alerts
|

Engineering T Cells Specific for a Dominant Severe Acute Respiratory Syndrome Coronavirus CD8 T Cell Epitope

Abstract: Severe acute respiratory syndrome (SARS) is a highly contagious and life threatening disease, with a fatality rate of almost 10%. The etiologic agent is a novel coronavirus, severe acute respiratory syndrome coronavirus (SARS-CoV), with animal reservoirs found in bats and other wild animals and thus the possibility of reemergence. In this study, we first investigated at 6 years postinfection whether SARS-specific memory T cells persist in SARS-recovered individuals, demonstrating that these subjects still poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 32 publications
4
92
0
Order By: Relevance
“…Recovered SARS individuals (6 y postinfection) were diagnosed with SARS based on clinical examination during the period from March to May 2003, according to the World Health Organization's definition of SARS (13). The diagnosis was further confirmed by serological detection of SARS-CoV-specific Abs by ELISA and/or RT-PCR for SARS-CoV mRNA, as described previously (14).…”
Section: Patient Samplesmentioning
confidence: 99%
“…Recovered SARS individuals (6 y postinfection) were diagnosed with SARS based on clinical examination during the period from March to May 2003, according to the World Health Organization's definition of SARS (13). The diagnosis was further confirmed by serological detection of SARS-CoV-specific Abs by ELISA and/or RT-PCR for SARS-CoV mRNA, as described previously (14).…”
Section: Patient Samplesmentioning
confidence: 99%
“…In humans, decreased T cell numbers (lymphopenia) correlated with severe disease, indicating the critical role of T cell-mediated immune response in disease development [11,12]. While SARS-specific antibody level in SARS-recovered individuals is undetectable at 6 years post-infection, SARS-specific memory T cells persisted up to 6 years following recovery [13]. The long-term persistence of memory T cell immunity could be important in protection against SARS-CoV re-infection.…”
Section: Introductionmentioning
confidence: 99%
“…The human HBV HBc protein-derived peptide HBc87-95 (SYVNT-NMGL) (Li et al, 2005) and SARS-CoV N protein-derived peptide N216-225 (GETALALLLL) (Oh et al, 2011) were synthesized with 95% purity by reverse-phase high performance liquid chromatography (SciLight Biotechnology, Beijing, China). The peptides were stored at −80°C as freeze-dried powders and were dissolved in dimethyl sulfoxide before use.…”
Section: Peptide Synthesis and Preparation Of Expression Constructsmentioning
confidence: 99%
“…Herein, by determining the crystal structures of human MHC I HLA-B*4001 complexed with a severe acute respiratory syndrome coronavirus (SARS-CoV) nucleocapsid (N)-derived T-cell epitope (Oh et al, 2011) and mouse MHC I H-2K d bound to an immunodominant T-cell epitope from human hepatitis B virus (HBV) core antigen (HBc) (Li et al, 2005), we clearly demonstrated the molecular features of MHC I molecules with two different salt bridges formed by the residues pairs Arg62-Glu163 and Arg66-Glu163, respectively. We further investigated the impacts of the salt bridges on peptide binding and T-cell recognition by constructing a series of MHC I mutants in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%